Triboelectric energy harvesting technology for self-powered personal health management - Yong Hyun Kwon; Xiangchun Meng; Xiao Xiao; In-Yong Suh; Daun Kim; Jaehan Lee; Sang-Woo Kim (International Journal of Extreme Manufacturing)
The global healthcare landscape is increasingly challenged by the rising prevalence of chronic diseases and the demographic shift towards an aging population, necessitating the development of innovative and sustainable healthcare solutions. In this context, the emergence of triboelectric energy harvesters as a key technological breakthrough offers a viable pathway towards self-powered, efficient, and sustainable personal health management. This review critically examines the transformative potential of triboelectric nanogenerators (TENGs) in addressing the pressing challenges of modern healthcare, underscoring their unique benefits such as being battery-free, easy to fabricate, and cost-efficient. We begin by reviewing the fundamental mechanisms of triboelectrification at the atomic scale and presenting the contact electrification among various materials, such as metals, polymers, and semiconductors. The discussion subsequently extends to the commonly used materials for TENGs and explores advancements in their design and functionality, with an emphasis on structural and chemical innovations. Furthermore, the application spectrum of TENGs in personal health management is extensively reviewed, covering aspects including health monitoring, therapeutic intervention, health protection, and device powering, while highlighting their capacity for self-sustainability. The review concludes by addressing existing challenges while mapping out the latest significant contributions and prospective directions in TENG-based healthcare innovations. By facilitating a paradigm shift towards a more autonomous, cost-effective, and personalized healthcare model, independent of external power sources, TENGs are poised to markedly enhance the quality of care and overall well-being, marking the dawn of a new era in integrated personal health management.